Evaluasi Hasil Produktivitas Alat Gali Muat Excavator PC-400 pada Proses Penambangan Batubara di PT. Artamulia Tatapratama - Mai Ridho Purnomo Putra; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Coal includes non-renewable resources originating from plants in an oxygen-free environment, and is subjected to the effects of pressure and heat that lasts very long. The coal mining process can be carried out using the Underground Mining and Surface Mining methods. The choice of mining method is based on the geological elements of coal. PT Artamulia Tatapratama is a Mining Contarctor company engaged in coal mining with the Surface Mining method. In a mining activity the mining operation starts from coal loading, transportation, to coal dumping in the stockpile. Production is a final target for companies in a mining process, where production has been planned by the company in advance. To produce production must take into account the mechanical readiness of the tool in a certain time, the use of tools and the number of products produced. To achieve the production of digging equipment is a very supporting factor in the mining process. Excavators used for coal mining are excavators. Excavator production achievement is influenced by bucket capacity, Bucket Fill Factor, Swell Factor, work efficiency, Cycletime of the tool. while the factors that greatly affect production are Human, Mechine, Method, Material and work environment.Keywords: Productivity, Excavator, Coal, Artamulia